SOSIALISASI HUKUM DIGITAL DI LINGKUNGAN PEMERINTAH KOTA ADMINISTRASI JAKARTA SELATAN MELALUI KERJA SAMA DENGAN ORGANISASI ADVOKAT PERATIN DALAM MENGHADAPI INDUSTRIALISASI DIGITAL DI INDONESIA - Mohamad Firdaus (CV. Denasya Smart Publisher, 2026)
Digital industrialization in Indonesia has driven significant changes in governance and public service delivery based on information technology. Local governments are required to adapt to digital transformation while ensuring compliance with applicable legal provisions. However, government officials' understanding of digital law still faces various limitations, particularly regarding personal data protection, electronic system security, and legal liability within the digital sphere. This Community Service (PKM) activity aims to enhance the literacy and digital legal awareness of officials within the Administrative City Government of South Jakarta through digital law socialization programs. This initiative was conducted in collaboration with the Indonesian Information Technology Advocates Association (PERATIN) as a digital law practitioner partner. The implementation methods included thematic presentations, interactive discussions, and case studies relevant to the challenges of digital industrialization in Indonesia. The results indicate an increase in participants' understanding of digital legal risks and the importance of implementing legal compliance principles to support secure and sustainable digital governance.